Assessing and Enhancing Health Care Providers’ Response to Domestic Violence - Tuija Leppäkoski; Aune Flinck; Eija Paavilainen (Nursing Research and Practice)
This study aimed to examine possible changes from 2008 to 2012 in the skills of health care staff in identifying and intervening in domestic violence (DV). A longitudinal descriptive study design with volunteer samples (baseline; n=68, follow-up; n=100) was used to acquire information regarding the present state and needs of the staff in practices related to DV. The results of the baseline survey were used as a basis for planning two interventions: staff training and drafting practical guidelines. Information was collected by questionnaires from nurses, physicians, and social workers and supplemented by responses from the interviews. The data were analysed using both quantitative and qualitative methods. A chi-square test was used to test the statistical significance of the data sets. In addition, participants’ quotes are used to describe specific phenomena or issues. The comparison showed that overall a small positive change had taken place between the study periods. However, the participants were aware of their own shortcomings in identifying and intervening in DV. Changes happen slowly, and administrative support is needed to sustain such changes. Therefore, this paper offers recommendations to improve health care providers’ response to DV. Moreover, there is a great need for evaluating the training programme used.